2011
DOI: 10.1002/ceat.201000271
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Natural Vitamin E Using a Continuous Countercurrent Supercritical CO2 Extraction‐Distillation Dual Column

Abstract: A continuous countercurrent supercritical CO 2 extraction-distillation dual-column process was developed to extract and concentrate natural vitamin E (VE) from soybean oil deodorizer distillate (SODD). The experimental results demonstrated that process parameters such as extraction pressure, temperature, and solvent-to-feed ratio significantly impacted on the extraction efficiency of natural VE. A new five-parameter mass transfer model for the continuous countercurrent supercritical CO 2 extraction-distillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Os processos usados industrialmente para a extração e purificação dos componentes dos DDs, bem como aqueles mais estudados visando sua otimização, envolvem diversas das etapas dentre as citadas a seguir: metanólise, etanólise ou glicerólise, destilação molecular, extração for fluido em estado supercrítico, extração e, coluna de recheio, cristalização e filtração sob vácuo (SHI et al, 2011;VAZQUEZ et al, 2007;ITO et al, 2005;YAN et al, 2012;FREGOLENTE et al, 2010).…”
Section: Conclusõesunclassified
“…Os processos usados industrialmente para a extração e purificação dos componentes dos DDs, bem como aqueles mais estudados visando sua otimização, envolvem diversas das etapas dentre as citadas a seguir: metanólise, etanólise ou glicerólise, destilação molecular, extração for fluido em estado supercrítico, extração e, coluna de recheio, cristalização e filtração sob vácuo (SHI et al, 2011;VAZQUEZ et al, 2007;ITO et al, 2005;YAN et al, 2012;FREGOLENTE et al, 2010).…”
Section: Conclusõesunclassified
“…A rapid extraction can be achieved by SFE and the vitamin E recovery was obtained up to 80% 29,32 . Some modification to increase the vitamin E recovery has been studied, such as the continuous stage of SFE 31,39 , dual column processing 33 and also the usage of co-solvent 30 which also can reduce the extraction time. Although SFE has been successful to obtain the high efficiency, clean environmentally process and solvent-freeresidue in the products 34,38 , it needs a high investment cost in the equipment of SFE 21 .…”
Section: 30 Vitamin E Extraction From Palm-based Oilsmentioning
confidence: 99%
“…Therefore, this can enhance the concentration of Vitamin E. Several researchers have studied the modified esterification as the pretreatment for the vitamin E separation. Combination of esterification with supercritical fluid extraction (SC-CO2) will improve the solubility of fatty acids and enhance the vitamin E obtained [32][33][34]36 . Shi et al 33 has reported that vitamin E contains in esterification of soybean oil deodorizer increased from 5wt-% in SODD to 20wt-% in their ester forms.…”
Section: 30 Vitamin E Extraction From Palm-based Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the deodorizer distillate is the main raw material for the production of natural tocopherols, sterols and so on. Tocopherol contains four isomers, named α, β, γ, and δ-tocopherol, and a mixture of α, γ, and δ-tocopherol is widely found in vegetable oils 2 . As an active substance with strong antioxidant and physiological function, tocopherols have attracted much more attention in many fields, such as food, pharmacy and cosmetics 3 6 .…”
Section: Introductionmentioning
confidence: 99%